Related issues of China Mobile LTE TDD/FDD fusion network - ANGZuyang W (Dianxin kexue)
The TD-LTE and LTE FDD fusion network is the trend of the future LTE network.With the further development of 4G network and the rdeuction of GSM network load,China Mobile will double existing GSM frequency resources for LTE FDD network construction.The LTE TDD/FDD fusion networking opportunities and challenges for the introduction of LTE FDD,GSM frequency reset strategy,the setting of interference isolation,antenna construction method and the selection of main equipment,and the future network structure optimazation problems,were analyzed.